RELIGIOUS BELIEFS OF CENTRAL ASIA IN THE 6TH–7TH CENTURIES AND THEIR INFLUENCE ON SOCIO-POLITICAL LIFE (The Journal of Interdisciplinary Human Studies, 2026)
The article is devoted to the investigation of research and scientific-theoretical approaches to the investigation of the Central Asian governance system. It discusses Central Asia’s history, ethnography, statehood, the judicial system and religious processes in the region.
Keywords: Central Asia, Khorasan, Movarounnahr, samanids, karakhanids, ghaznavids, seljuks, khorezmshahs, qarluqs, oguzs, ajam.